Adverse perinatal outcomes associated with timing of initiation of antiretroviral therapy: systematic review and meta-analysis - Sexton, H; Kumarendran, M; Brandon, Z; Shi, C; Kirtley, S; Hemelaar, J (Wiley, 2022)
Background The World Health Organisation (WHO) recommends immediate initiation of lifelong antiretroviral therapy (ART) for all people living with HIV, including pregnant women. As a result, an increasing number of women living with HIV (WLHIV) conceive while taking ART, the vast majority of whom reside in low- and middle-income countries (LMICs). We aimed to assess the association between timing of ART initiation and perinatal outcomes. Methods We conducted a systematic literature review by searching PubMed, CINAHL (Ebscohost), Global Health (Ovid), EMBASE (Ovid), and the Cochrane Central Register of Controlled Trials and four clinical trial databases (WHO International Clinical Trials Registry Platform, the Pan African Clinical Trials Registry, the ClinicalTrials.gov database, and the ISRCTN Registry) from Jan 1, 1980 to April 28, 2018. We identified studies reporting specific perinatal outcomes among pregnant WLHIV according to timing of ART initiation and extracted data. Perinatal outcomes assessed were preterm birth (<37 weeks), very preterm birth (<32 weeks), low birthweight (<2500g), very low birthweight (<1500g), small for gestational age (<10th centile), very small for gestational age (<3rd centile) and neonatal death (<29 days). Random-effects meta-analyses examined perinatal outcomes associated with preconception and antenatal ART initiation, as well as according to trimesters of antenatal initiation. We performed quality assessments, subgroup and sensitivity analyses, and assessed the effect of adjustment for confounders. This systematic review and meta-analyses is registered with PROSPERO, number CRD42021248987. Results Of 51,874 unique citations, 25 studies (8 prospective and 17 retrospective cohort studies) were eligible for analysis, including 40,920 WLHIV. Preconception ART initiation was associated with a significantly increased risk of preterm birth (relative risk 1.16, 95% CI 1.03-1.31), compared to antenatal ART initiation. Preconception ART initiation was not significantly associated with very preterm birth, low birthweight, very low birthweight, small for gestational age, very small for gestational age, or neonatal death. First trimester exposure (i.e. preconception or first trimester initiation) was not significantly associated with any increased risk of adverse perinatal outcomes. No significant association between timing of ART initiation and adverse perinatal outcomes was found in the studies of higher quality and those conducted in LMICs. Conclusion Preconception ART initiation is associated with preterm delivery, but no other perinatal outcomes. In LMICs, where most pregnant WLHIV reside, the timing of ART initiation was not associated with any adverse perinatal outcomes.